Gas phase RDX decomposition pathways using coupled cluster theory. Issue 37 (9th September 2016) - Molt, Robert W.; Watson, Thomas; Bazanté, Alexandre P.; Bartlett, Rodney J.; Richards, Nigel G. J.
Abstract : Electronic and free energy barriers for a series of gas-phase RDX decomposition mechanisms have been obtain using coupled cluster singles, doubles, and perturbative triples with complete basis set (CCSD(T)/CBS) electronic energies for MBPT(2)/cc-pVTZ structures. Abstract : Electronic and free energy barriers for a series of gas-phase RDX decomposition mechanisms have been obtain using coupled cluster singles, doubles, and perturbative triples with complete basis set (CCSD(T)/CBS) electronic energies for MBPT(2)/cc-pVTZ structures. Importantly, we have located a well-defined transition state for NN homolysis, in the initial RDX decomposition step, thereby obtaining a true barrier for this reaction. These calculations support the view that HONO elimination is preferred at STP over other proposed mechanisms, including NN homolysis, "triple whammy" and NONO isomerization. Indeed, our calculated values of Arrhenius parameters are in agreement with experimental findings for gas phase RDX decomposition. We also investigate a number of new pathways leading to breakdown of the intermediate formed by the initial HONO elimination, and find that NN homolysis in this intermediate has an activation energy barrier comparable with that computed for HONO elimination.